2018
DOI: 10.3390/ijms19020506
|View full text |Cite
|
Sign up to set email alerts
|

Tea Polysaccharide Prevents Colitis-Associated Carcinogenesis in Mice by Inhibiting the Proliferation and Invasion of Tumor Cells

Abstract: The imbalance between cell proliferation and apoptosis can lead to tumor progression, causing oncogenic transformation, abnormal cell proliferation and cell apoptosis suppression. Tea polysaccharide (TPS) is the major bioactive component in green tea, it has showed antioxidant, antitumor and anti-inflammatory bioactivities. In this study, the chemoprophylaxis effects of TPS on colitis-associated colon carcinogenesis, especially the cell apoptosis activation and inhibition effects on cell proliferation and inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 45 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…Excessive ROS production induces aberrant NF-κB activation that cause inflammatory bowel disease (IBD) or colitis-associated cancer (CAC) [ 12 , 13 ]. Some studies have shown that the intake of antioxidants inhibits IBD and CAC in mouse models [ 14 , 15 , 16 ]. In particular, the antioxidant ergothioneine scavenges intestinal oxidative stress after intracellular uptake by the organic carnitine transporter (OCTN1), which is expressed in the intestine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive ROS production induces aberrant NF-κB activation that cause inflammatory bowel disease (IBD) or colitis-associated cancer (CAC) [ 12 , 13 ]. Some studies have shown that the intake of antioxidants inhibits IBD and CAC in mouse models [ 14 , 15 , 16 ]. In particular, the antioxidant ergothioneine scavenges intestinal oxidative stress after intracellular uptake by the organic carnitine transporter (OCTN1), which is expressed in the intestine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effective components in tea can cause cell cycle arrest, and inhibit the proliferation of cancer cells (Figure 4). Tea polysaccharides from green tea can arrest the cell cycle via the down‐regulation of cyclin D1 in AOM/DSS‐induced colorectal carcinogenesis in mice, 33,34 make MCF‐7 cancer cells undergo G2/M phase arrest by up‐regulating p53 (also known as a tumor suppressor gene), 29 and reduce cell proliferation through down‐regulating the Akt/ERK signaling pathway in prostate cancer cells and tissues 75 . Theaflavins and thearubigins can induce cell cycle arrest at the G0/G1 or G1/S phase in human leukemic cells (U937 and K562) and ovarian cancer cells (A2780/CP70 and OVCAR‐3) by ablating cyclin‐dependent kinases (CDKs) and cyclin D1 levels, which were regulated by heat shock protein (HSP) 90, protein kinase B (Akt) signaling, wingless‐type MMTV integration site family (Wnt)/β‐catenin signaling, p21 and forkhead transcription factor 1 (FOXO1) 76,77 .…”
Section: Anti‐cancer Mechanisms Of Tea and Its Functional Componentsmentioning
confidence: 99%
“…[22][23][24] Moreover, the anti-cancer activity of tea mainly depends on its functional constituents. Several in vivo and in vitro studies have shown that tea polyphenols (especially epigallocatechin-3-gallate [EGCG]), [25][26][27][28] tea polysaccharides, [29][30][31][32][33][34] Ltheanine, [35][36][37] tea pigments, 38 and caffeine 39,40 can inhibit the occurrence and development of cancers. Conversely, there are few studies focused on the minor constituents (such as tea saponin, tea protein, vitamins, fat, trace elements, γ-aminobutyric acid, and enzymes) and their potential to prevent cancer.…”
Section: The Anti-cancer Role Of Tea Componentsmentioning
confidence: 99%
“…The nuclei were counterstained with DAPI and slides were photographed using Zeiss Axio microscope. Sections were evaluated focusing on longitudinally oriented crypts and the number of Ki-67-positive cells per HPF (40× objective) were counted [61,62].…”
Section: Histological Studiesmentioning
confidence: 99%